Examining Brexit: Level of Analysis and Explanations (Comillas Journal of International Relations, 2021)
This article analyses the scholarly debate on the Brexit phenomenon and its possible causes. By contextualizing Brexit in the International Relations Theory debate about the levels of analysis, the article focuses on some of the most recent contributions of the Brexit literature. Firstly, it analyses the contributions that explain Brexit as a problem of international and European politics, related to the adaptation of the United Kingdom to the process of European integration. Secondly, it analyses the contributions that explain Brexit as the result of causes located at the domestic level, such as the decisions and perceptions of national leaders, the decision-making process, and the impact of populist and Eurosceptic political discourse. The article identifies the advantages of an approach capable of considering both international and domestic variables. This allows a deeper understanding of the phenomenon and a potentially fruitful collaboration between political scientists from different disciplines, such as International Relations Theory and Comparative Politics.
Keywords: Brexit; international relations theory; foreign policy analysis; comparative politics